Concept of Investigation and Reform of Serbian Criminal Procedural Law - Čvorović, Dragana; Lajić, Oliver (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The topic of this article is a critical analysis of professional issues in the investigation of the concept of reform of the criminal procedure legislation in Serbia, which is still ongoing. Underlying issues have been analysed from three aspects. First, general comments about the investigation and its relevance to criminal proceedings are provided, and within those, the issues for a long period of criminal procedure are discussed in theory and practice. For example, there is a case to investigate the relationship between the concept and its effectiveness and thus the efficiency of the process as a whole. The second aspect of the analysed issues consist of questions related to the concept of prosecutorial investigation as an essential feature of the process of reform of the criminal procedure legislation in Serbia, where arguments of prosecutorial justification of the concept of judicial investigation have primarily been analyzed along with the principles by which a legislator should be guided in the standardization of the prosecutorial concept of investigation. Finally, the third – and the key aspect consists of the issues related to the review of normative elaboration of the concept of prosecutorial investigation into the new RS CPC and the draft Law on Amendments to the legal text available to the Serbian expert public, and not just Serbian. The main conclusion of expert critical analysis of this group of questions, which are still in the draft of the Law on Amendments to the CPC concept of prosecutorial investigation in Serbia, is that it develops in a way that is consistent with the efforts of the majority of experts in Serbia and not only in Serbia.